2021
DOI: 10.3390/buildings11080344
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Hydraulic Analysis of High-Rise Building Wastewater Drainage Networks: Modelling Basis

Abstract: A model is presented which allows steady-state pressure profiles in high-rise wastewater drainage networks to be related to intake air flowrates and discharge water flowrates. This model is developed using data taken from academic literature, and is based on experimental observations which suggest that a vertical annular downflow develops over distance such that the pressure gradient in the wet stack may be expressed as the sum of junction components and developed flow components. The model is used to analyse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A hanging gardens algorithm was applied to optimize drainage networks in the urban drainage system; the optimization variables include the size and number of pipelines 16 . Steady‐state pressure of intake air flowrates was studied in the design of wastewater drainage networks 17 . Model predictive control was applied on the urban drainage system (UDS) to reduce the pollution of combined sewer overflow (CSO) and show the effects of the rainfall forecasting 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hanging gardens algorithm was applied to optimize drainage networks in the urban drainage system; the optimization variables include the size and number of pipelines 16 . Steady‐state pressure of intake air flowrates was studied in the design of wastewater drainage networks 17 . Model predictive control was applied on the urban drainage system (UDS) to reduce the pollution of combined sewer overflow (CSO) and show the effects of the rainfall forecasting 18 .…”
Section: Introductionmentioning
confidence: 99%
“…16 Steady-state pressure of intake air flowrates was studied in the design of wastewater drainage networks. 17 Model predictive control was applied on the urban drainage system (UDS) to reduce the pollution of combined sewer overflow (CSO) and show the effects of the rainfall forecasting. 18 Partial differential equations are formulated on the flow dynamics in the pipelines of wastewater network and applied on urban drainage.…”
mentioning
confidence: 99%
“…The recent COVID-19 pandemic has highlighted the importance of the building drainage system (BDS) in securing public health. Recent research has shown that pathogens such as SARS and SARS Cov-2, which cause COVID-19, as well as laboratory surrogate pathogens such as pseudomonas putida (bacterium) and PMMoV (virus), can be transmitted through the air core of the annular flow inside the BDS [1][2][3][4][5]. The flow regime in a drainage system is generated by the unsteady transient flow of a free-falling annular flow, which is a simplified version of a twophase annular flow with zero or natural airflow.…”
Section: Introductionmentioning
confidence: 99%
“…Recent analyses have indicate that design water flowrates, which tend to be based on supply of flow to a stack and not actual flow in a stack, are over-conservative and should be revised downwards (Omaghomi et al [10], Mohammed et al [11]). The development of instrumentation to measure the downward annular air-water flow which is prevalent in tall stacks, and the development of models which describe the underlying physics of this flow are ongoing (Xue et al [12], Stewart et al [13]). The importance of this research has been highlighted by the recent Sars-Cov-2 (COVID-19) pandemic and substantial evidence linking the spread of pathogens to depletions of water trap seals with tall buildings (e.g., [14][15][16][17]).…”
Section: Introduction 1historical Developmentmentioning
confidence: 99%